Imagination In Lucy Maud Montgomerys Novel Anne OfGreen Gables (1908) : A Psychoanalytic Approach - Hanifah, Rizky; Candraningrum, S.Pd, Med, Dr. Phil. Dewi Candraningrum, S.Pd, Med (2016)
The major issue of this study is imagination. The objective of this study is to analyze Lucy Maud Montgomerys Anne of Green Gables novel based on the structural elements and analyze this novel based on the Psychoanalytic Approach. The writer employs descriptive qualitative method. The primary data of the research is Anne of Green Gables novel by Lucy Maud Montgomerys. Then the secondary data of the research are taken from about psychoanalysis, references information related to the novel from novel from other books, references about imagination theory, and internet. The techniques of collecting data are reading the novel. The method of data collection is library research and the technique of data collection is descriptive technique. In the novel titled Anne of Green Gables, Anne's type personality as an orphan who never get a real affection from another person before, tries to survive with all her imagination. At this time, Lucy Maud Montgomery shows about Anne's effort to alive defensively. Based on the analysis, the researcher gets some conclusion. Anne Shirley has extremely imagination in a lot of aspect of her life. Anne Shirley has spirit and never give up about her dream. Little Anne, someday wants to be a teacher.